علماء المسلمين وإسهامم في الحضارة الإنسانية - Bahjat, Mujahid Mustafa; Sabu’i, Salih (Journal of Al-Tamaddun, 2009)
This research aims to clarify the efforts of the Muslim Scholars in the Human Civilization in general, and specifically the European one; and this clarification will be done through the testimony of the western orientalist, Sigrid Hunke (d. 1999) in her book ? Allah`s Sun Over The Occident?. To clarify her testimony regarding the contributions of the Muslim Scholars in the Western Civilization, this research comes into two parts and a conclusion. Part One: It clarifies the true nature of her testimony; and that through three fields: a- Field of theoretical and applied sciences. b- Field of Manners and Etiquette. c- Field Development and Urbanization. Part two: It includes comments and remarks regarding the aforesaid testimony, and mention out the factors behind the arising of the Islamic Civilization which then affect on the Human Civilization. We hope through this testimony of the contributions of Muslim scholars in various fields of the human civilization to motivate the successors to fellow the path of science and knowledge of their ancestors.